QUANTIZATION OF DIFFEOMORPHISM INVARIANT THEORIES OF CONNECTIONS WITH LOCAL DEGREES OF FREEDOM - Ashtekar, Abhay; Lewandowski, Jerzy; Marolf, Donald; Mourao, José Manuel; Thiemann, Thomas (Journal of Mathematical Physics, 1995)
Quantization of diffeomorphism invariant theories of connections is studied and the quantum diffeomorphism constraint is solved. The space of solutions is equipped with an inner product that is shown to satisfy the physical reality conditions. This provides, in particular, a quantization of the Husain-Kuchar model. The main results also pave the way to quantization of other diffeomorphism invariant theories such as general relativity. In the Riemannian case (i.e., signature ++++), the approach appears to contain all the necessary ingredients already. In the Lorentzian case, it will have to be combined in an appropriate fashion with a coherent state transform to incorporate complex connections. (C) 1995 American Institute of Physics.